2021
DOI: 10.15294/eeaj.v10i3.50437
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Interactive Multimedia Android-Based Archiving Towards Learning Independence

Abstract: This research aims to find out the use of interactive multimedia archiving based on android and its effect on the learning independence of vocational learners. Research is a type of research and development (R & D). Research methods using experiments are pretend experiments (Quaisy experiment). The research was conducted at Vocational High School Surakarta City in April-June 2021. The population in this study is all students of class X Vocational High School Surakarta school year 2020/2021. The sample used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(5 reference statements)
1
0
0
Order By: Relevance
“…Digital-based learning media using the latest technology according to the times faced by students, which will be able to increase student learning motivation and learning, becomes more interesting for students because they feel they are in their world, and then the output will improve student learning outcomes. These results are supported by research Dewi, et al (2019); Dirgatama, et al (2021); Martanti & Rusdarti (2019); Yektyastuti & Ikhsan (2016), which revealed that the developed learning media could increase students' motivation in learning and cognitive learning outcomes because the media was developed in accordance with the students' thinking level.…”
Section: Develop (Development)supporting
confidence: 61%
“…Digital-based learning media using the latest technology according to the times faced by students, which will be able to increase student learning motivation and learning, becomes more interesting for students because they feel they are in their world, and then the output will improve student learning outcomes. These results are supported by research Dewi, et al (2019); Dirgatama, et al (2021); Martanti & Rusdarti (2019); Yektyastuti & Ikhsan (2016), which revealed that the developed learning media could increase students' motivation in learning and cognitive learning outcomes because the media was developed in accordance with the students' thinking level.…”
Section: Develop (Development)supporting
confidence: 61%